Higher education in ukraine during war - Ivanchenko, O. Z.; Lurie, K. I.; Melnikova, O. Z.; Іванченко, Олена Зенонівна; Лур'є, Костянтин Ігорович; Мельнікова, Оксана Зенонівна (My University, 2023)
The article covers the definition of several problems that arose in society and higher education in Ukraine since the beginning of the war. Several scientific publications were analyzed to determine the most optimal organization for continuous education.
Keywords: education during war; continuity of education; security